2021
DOI: 10.3389/fphar.2021.688528
|View full text |Cite
|
Sign up to set email alerts
|

Explore the Usefulness of Concurrent Chemotherapy in Stage II Nasopharyngeal Carcinoma: A Retrospective Study

Abstract: Objective: This study aims to compare the treatment outcomes of concurrent chemoradiotherapy (CCRT) versus radiotherapy (RT) alone in stage II nasopharyngeal carcinoma (NPC) patients.Methods: We retrospectively collected 601 stage II NPC patients treated in two hospitals between June 2003 to June 2016. All patients were divided into the CCRT group (n = 255) and the RT group (n = 346). Overall survival (OS), locoregional failure-free survival (LRFFS), progression-free survival (PFS), and distant metastasis-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…The stability of the results was evaluated by removing some studies according to different standards ( Table 3 ). First of all, the sensitivity analysis was conducted in IMRT studies by separately eliminating two studies ( 8 , 35 ) with a sample size of less than 100 patients, four studies ( 11 , 32 , 33 , 35 ) with a median follow-up time of fewer than 60 months, and three studies ( 11 , 33 , 34 ) that included concurrent chemotherapy regimens other than cisplatin, respectively. It suggested that OS, LRFS, DMFS, and PFS were similar between the CCRT group and IMRT alone group, which was consistent with that before sensitivity analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The stability of the results was evaluated by removing some studies according to different standards ( Table 3 ). First of all, the sensitivity analysis was conducted in IMRT studies by separately eliminating two studies ( 8 , 35 ) with a sample size of less than 100 patients, four studies ( 11 , 32 , 33 , 35 ) with a median follow-up time of fewer than 60 months, and three studies ( 11 , 33 , 34 ) that included concurrent chemotherapy regimens other than cisplatin, respectively. It suggested that OS, LRFS, DMFS, and PFS were similar between the CCRT group and IMRT alone group, which was consistent with that before sensitivity analysis.…”
Section: Resultsmentioning
confidence: 99%
“…IMRT has become a daily choice for NPC. Several studies (8,11,(32)(33)(34)(35)(36) have investigated whether concurrent chemotherapy can further improve the efficacy of stage II NPC patients receiving IMRT. However, the results of these studies are not completely consistent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The locoregional control rate of NPC has markedly improved since the widespread use of IMRT [5], challenging the role of CCT as part of the treatment. Several studies revealed that the combination of NCT plus IMRT was as effective as NCT plus CCRT for managing locally advanced NPC [17][18][19]. However, most studies are limited by inconsistent chemotherapy regimens and NCT cycles, making it difficult to draw convincing conclusions.…”
Section: Discussionmentioning
confidence: 99%